Classification of alcohol use disorders among nightclub patrons: associations between high-risk groups, sociodemographic factors and illicit drug use. (3rd September 2015) - Santos, Raissa; Baldin, Yago; Carlini, Claudia M.; Sanchez, Zila M.
Abstract: Background : Nightclubs are favorable environments for alcohol abuse and the use of other drugs among patrons. Objective : To identify patterns of alcohol use in a high-risk population and their relationship with sociodemographic factors and illicit drug use. Methods : A portal survey technique was used to recruit patrons in 31 nightclubs in the city of São Paulo, Brazil. A two stage sampling method allowed the selection of nightclubs and patrons within a nightclub. A total of 1057 patrons answered to a three stages-survey (nightclub entrance and exit face-to-face interviews and a day-after online questionnaire). Entrance survey offered information on sociodemographic data and history of drug use. The day-after survey used the Alcohol Use Disorders Identifications Test (AUDIT) that identified patterns of alcohol abuse disorders. Data were modeled using an ordered logit regression analysis, considering sample weights. Results : Almost half of the nightclub patrons presented any alcohol use disorder (AUDIT score ≥8). Being male (OR = 1.68; 95% CI = 1.09–2.60) and single (OR = 1.71; 95% CI = 1.05–2.76) increased the chances for more severe alcohol use disorders. Having a graduate degree (OR = 0.57; 95% CI = 0.38–0.87) and age ≥35 years (OR = 0.48; 95% CI = 0.27–0.85) decreased the chances of patrons' alcohol use disorders. The prevalence rates of past-year marijuana, cocaine and inhalants use increased with the increased level of alcohol use disorders. Conclusions : Patrons of nightclubs show higher prevalence rates for any alcohol use disorders than the general population. Patrons could benefit from governmental brief intervention or referral to treatment for alcohol used disorders disclosed in nightclubs.